2020
DOI: 10.1002/rcm.8636
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 6‐bromoferulic acid as a novel common‐use matrix for matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry

Abstract: Rationale Ferulic acid (FA) is a standard matrix used for analyzing proteins. In this study, the ability of a halogenated FA to serve as an effective MALDI matrix was investigated. Various halogenated FAs were synthesized, and the characteristics and performance of each were compared with those of the standard matrices α‐cyano‐4‐hydroxycinnamic acid (CHCA) and 2,5‐dihydrobenzoic acid (DHBA). Methods The abilities of 6‐bromoferulic acid (6‐BFA), ferulic acid (FA), and eight other halogenated FA derivatives to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…[M + alkali metal] + ions were formed with carbohydrates and, using fructose, the authors found that the peak intensity decreased with increasing atomic weight of the adduct (Li–Cs). Following the observation that introduction of chlorine into the 4‐position of CHCA improved its performance, Kato et al (2020) have investigated the effect of adding halogens to the matrix ferulic acid, sometimes used for proteins. 6‐Bromoferulic acid ( 14 ), although exhibiting improved sensitivity for acidic proteins, was found not to produce signals from carbohydrates either in positive or negative ion modes.…”
Section: Matricesmentioning
confidence: 99%
“…[M + alkali metal] + ions were formed with carbohydrates and, using fructose, the authors found that the peak intensity decreased with increasing atomic weight of the adduct (Li–Cs). Following the observation that introduction of chlorine into the 4‐position of CHCA improved its performance, Kato et al (2020) have investigated the effect of adding halogens to the matrix ferulic acid, sometimes used for proteins. 6‐Bromoferulic acid ( 14 ), although exhibiting improved sensitivity for acidic proteins, was found not to produce signals from carbohydrates either in positive or negative ion modes.…”
Section: Matricesmentioning
confidence: 99%